Dynamic behavior of droplet transport on realistic gas diffusion layer with inertial effect via a unified lattice Boltzmann method. (24th September 2021) - Yang, Jiapei; Fei, Linlin; Zhang, Xiaoqing; Ma, Xiao; Luo, Kai H.; Shuai, Shijin
Abstract: The dynamic behavior of liquid droplets on a reconstructed real gas diffusion layer (GDL) surface with the inertial effect produced by the three dimensional (3D) flow channel is investigated using an improved pseudopotential multiphase model within the unified lattice Boltzmann model (ULBM) framework, which can realize thermodynamic consistency and tunable surface tension. The microstructure of the GDL (Toray-090) including carbon fibers and polytetrafluoroethylene (PTFE) is reconstructed by a stochastic and mixed-wettability model. The critical force formulation for the Cassie-Wenzel transition of a droplet on GDL surface is derived. The effects of inertia and contact angles on the liquid droplet transport process on a reconstructed real GDL surface with a 3D flow channel are investigated. The results show the normalized center-of-mass coordinate X may enter the channel wall area or fluctuate around the initial position. With increased inertia applied on the droplet, the normalized center-of-mass coordinate Y grows faster and the normalized center-of-mass coordinate Z decreases. It is found by the ULBM for the first time that the liquid droplet is pushed back into the GDL by inertial effect. With the increase of inertia and the decrease of contact angle of GDL, both the droplet penetration depth in GDL and the droplet invasion fraction increase. The droplet invasion fraction in GDL is up to 30%. Graphical abstract: Image 1 Highlights: An improved pseudopotential multiphase model within the ULBM framework is adopted. The role of inertial effect on droplets on a real GDL surface is revealed. The effect of surface wettability on droplet dynamics on the GDL surface is studied.